ANALISIS HUBUNGAN MOTIVASI TERHADAP KINERJA PEGAWAI (Studi Kasus Pada Kantor Kecamatan Ruing Kabupaten Ngada NTT) - Rawi, Rais Dera Pua (Jurnal Noken: Ilmu-Ilmu Sosial, 2017)
This study aims to determine the Relationship Motivation Against Employees Performance at the Office District Riung Ngada NTT, both partially and to determine which variables are most dominantly related to employee performance. Approach used in this study is Cross Sectional Study, with research type is research Analytical Survey .. Population as well as samples in this study as many as 30 employees at the district office Riung Ngada district NTT.The results showed that (1) There is a significant relationship incentive with the performance of employees at the district office Riung Ngada NTT. This is indicated by Chi-square value 4,176 â‰¥ 3,841. (2) No significant relationship Allowance with employee performance at the Rinung sub-district office Ngada NTT.Hal is shown with the value of Chi-square 0,517 <3.841. (3) There is no significant correlation of reward with employee performance at Riung District office of Ngada District NTT.Hal is shown by Chi-square 2,308 <3,841. The statistic test with Chi-square shows that incentives are highly related to 4.176%. As for the variable allowance of 0,517% and the variable of appreciation 2,308%, these two variables are not related to employee performance.